2018
DOI: 10.21325/jotags.2018.193
|View full text |Cite
|
Sign up to set email alerts
|

Restoran Çalışanlarının Algılamış Oldukları Örgütsel Güven Düzeylerinin Örgütsel Vatandaşlık ve İş Performansına Etkisi: Eskişehir Örneği (The Impact of Levels of Organizational Trust Perceived by Restaurant s Employees on Organizational Citizenship and Business Performance: The Case of Eskişehir)

Abstract: Bu araştırmanın amacı restoran çalışanlarının algılamış oldukları örgütsel güven düzeylerinin örgütsel vatandaşlık ve iş performansı üzerinde etkisi olup olmadığını tespit etmektir. Araştırma, benzer ürünleri veya hizmetleri sunan birçok işletmenin bulunduğu yiyecek içecek sektöründe faaliyet gösteren restoranlara önerilerde bulunmaktadır. Bu öneriler çalışanların örgüte olan bağlılığının, güveninin ve performansının artması ve işletmelerin verimliliğinin ve rekabet edilebilirliğinin geliştirilmesi açısından o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Envergil (2018) found the relationship of psychological contract perceptions to organizational trust and organizational citizenship behavior to be moderate. Cankül et al (2018) found that organizational trust positively affects organizational citizenship behavior and job performance. The study also revealed that organizational citizenship behavior positively affects job performance.…”
Section: Relationship Between Organizational Trust and Organizational Citizenship Behaviormentioning
confidence: 99%
“…Envergil (2018) found the relationship of psychological contract perceptions to organizational trust and organizational citizenship behavior to be moderate. Cankül et al (2018) found that organizational trust positively affects organizational citizenship behavior and job performance. The study also revealed that organizational citizenship behavior positively affects job performance.…”
Section: Relationship Between Organizational Trust and Organizational Citizenship Behaviormentioning
confidence: 99%